The Right To Development Or The Right To Migration-The Roots Of The Phenomenon Of Illegal Migration In African Sahelian Countries – - Lakehal Saliha , Ait Ahmed Lamara Mohamed (Migration Letters, 2024)
The study includes one of the important topics of concern to researchers, academics, and rapporteurs, namely illegal cross-border migration, which is considered a direct asymmetric threat. The study deals with the reality of this threat between Africa and Europe, i.e., migration from southern Africa to northern Europe. It is in three main axes that study the roots of i[1]llegal immigration from the countries of the Sahel, and Africa in general to Europe from the angle of the loss of the right to development, the primary motive for migration and the search for the most appropriate way of life, that is to say, with the loss of the fundamental right allowed the right to seek the best outside national borders. The study of the Afro-European model through a set of agreements, treaties, and meetings that have been concluded over many periods of time, whose main axes have always been the phenomenon of illegal immigration and how to solve it.